Effect of Dietary supplementation of Area Specific Mineral Mixture along with Hormonal Interventions on the Performances of the Anoestrous and Repeat Breeding Crossbred Cattle - Sethy, Kamdev; Behera, A. K.; Swain, R. K.; Mishra, S. K.; Behera, K.; Mishra, P. C. (Indian Journal of Animal Nutrition, 2019)
A study was conducted to assess the effect of area specific mineral mixture and hormonal therapy on the reproductive performances of anoestrous and repeat Breeding cross bred cattle of Nimapara block of Puri district, Odisha, India. A total of 60 animals (40 cows, 20 heifers) were selected and were divided into four groups of 15 animals each (containing both anoestrus and repeat breeder) in which treatment was performed for 60 days. Group I: control (farmer practice, straw based diet along with concentrates), group II: group I + area specific mineral mixture @ 50 g/animal/day, group III: group II + hormone (double synch), and group IV: group II + hormone (estra double synch). The growth performances were measured in terms of body weight and average daily gain (ADG). Blood collection was done at the start and end of the experiment for assessment of blood biochemical, hematological and mineral status of the animals. Results revealed significant improvement in growth and reproductive performances in treatment groups as compared to control group. So it may be concluded that supplementation of area specific mineral mixture along with hormones gave better result in augmenting reproductive disorder in cross bred animals.